Digital Humanities 2012 - Conference Abstracts. University of Hamburg, Germany; July 16-22, 2012 - Alliance of Digital Humanities Organizations, The; Association for Computers and the Humanities, The (Hamburg University Press, 2012)
'Digital Diversity: Cultures, Languages and Methods' is the motto for this year's Digital Humanities conference; it relates methodical and technical innovation to the traditional research agenda of the Humanities. The conference schedule includes contributions on a wide range of topics, reflecting the increasing breadth in the field on all levels. A recurring theme at Digital Humanities conferences in recent years has been the high number of submissions, and this year has continued the upward trend, with close to 400 submissions across the different categories: pre-conference workshops/tutorials, long papers, short papers, posters and multipaper sessions (including panels). This Book of Abstracts shows the diversity of this year's conference. The PDF version is freely available (open access; please download the file "HamburgUP_dh2012_B-o-A.pdf"). An elaborated version of the Book with color photos and zoom function is available at http://www.dh2012.uni-hamburg.de/conference/programme/abstracts/.